Evaluating the structural reform of outpatient psychotherapy in Germany (ES-RiP trial) - a qualitative study of provider perspectives - Poß-Doering Regina; Hegelow Martin; Borchers Milena; Hartmann Mechthild; Kruse Johannes; Kampling Hanna; Heuft Gereon; Spitzer Carsten; Wild Beate; Szecsenyi Joachim; Friederich Hans-Christoph (BMC, 2021)
Abstract Background Access to outpatient mental healthcare can be challenging for patients. In Germany, a national structural reform was implemented in 2017 to accelerate and enhance access to outpatient psychotherapy and reduce waiting times. During the first phase of the study 'Evaluation of a structural reform of the outpatient psychotherapy guideline (ES-RiP)' and embedded into a process evaluation, the implementation was to be evaluated through assessing general practitioners' (GPs) and psychotherapists' (PTs) perspectives regarding utilization of provided new measures, and perceived potential for optimization. Particular focus was on patients with a comorbidity of mental disorders and chronic physical conditions (cMPs). Methods This exploratory cross-sectional qualitative study used on-site and online focus group discussions and semi-structured telephone interviews with GPs and outpatient PTs. Generated data were analyzed using thematic framework analysis. Descriptive statistics were used to analyze participant characteristics collected via a socio-demographic questionnaire. Results Perspectives on the structural reform were heterogenous. GPs and PTs considered the component of timely initial psychotherapeutic assessment consultations beneficial. GPs disapproved of their deficits in detailed information about the structural reform and exchange with outpatient PTs. Improvement suggestions included structured short information exchange and joint quality circles. The overall number of available outpatient PTs in rural areas was perceived as insufficient. For patients with cMPs, GPs saw patient barriers for therapy access and continuity in low intrinsic motivation, physical impediments and older age. PTs also saw patient challenges regarding low intrinsic motivation and keeping scheduled appointments. They considered post-reform administrative efforts to be high and reported that the regulations (conformity) lead to planning difficulties and financial losses. Reform elements were tailored to fit in with PTs key therapy areas. Stronger networking and joint lectures were suggested as remedy for the currently still limited exchange with GPs. Unlike the GPs, PTs emphasized that accepting patients into psychotherapeutic treatment was independent of a possibly present chronic physical disease. Conclusions The findings contribute to understanding the integration of the delivered structural reform into daily care processes and provide an indication about reached targets and potential improvements. Further phases of the ES-RiP study can build on the findings and broaden insights. Trial registration Registration-ID DRKS00020344 (DRKS German Register of Clinical Trials.